Age, smoking, hypertension, and aortic aneurysm: Interactions and risks - SA, Seriki; OC, Otoikhila (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background/Aim: Aortic aneurysm is the bulging of a weakened portion of the aorta. The aorta is the major blood vessel that feeds blood (carrying oxygen, nutrients and water) to the tissues of the body. When a portion of the wall of the aorta becomes weak, blood pushing against the vessel wall can cause it to bulge like a balloon (aneurysm) leading to aortic dissection (a tear in the wall of the aorta that can cause life-threatening bleeding or sudden death). Blood pressure is the force arterial blood exerts on the wall of the artery. When this pressure is consistently high above 140/100 mmHg it is referred to as hypertension. As an individual gets older over time, physiological functions of the body depreciate leading to some abnormalities. Smoking is the consumption of tobacco mostly by inhalation of the smoke that is produced from burning the tobacco. This review article examines the close interactions between age, smoking, hypertension and aortic aneurysm, with a view to understanding mechanisms by which these factors predispose a patient to an aortic aneurism. It is also to observe if these factors interfere with treatment and recovery from aneurysms. Conclusion: After careful review, it is observed that age and smoking are risk factors for hypertension, and together with hypertension, the three factors predispose an individual to high risk for aortic aneurysm.